Socio-Demographic Determinants of Junk Food Consumption among University Students: A Cross-Sectional Study in Central Department of Education, TU - Pokhrel, Mahesh; Upreti, Yadu R.; Aryal, Bhagwan (Interdisciplinary Research in Education, 2024)
College life is a critical period during which students are particularly vulnerable to developing unhealthy dietary behaviors. This study assessed the socio-demographic determinants of junk food consumption (JFC) among higher education students. A quantitative cross-sectional study was conducted using a self-administered survey questionnaire among 272 university students studying at the Central Department of Education, TU. The findings revealed that although only six percent of students preferred to consume junk food, a surprisingly high proportion (83.5%) reported consuming it. Peer pressure was mentioned by nearly half of them (47.8%) as the main cause of JFC. Bivariate analysis showed a significant relationship between JFC and selected socio-demographic variables, including sex (p<0.05), subject specialization (p<0.001), and caste/ethnicity (p<0.05). The results indicate a high prevalence of JFC among university students, with socio-demographic factors such as sex, subject specialization, and caste/ethnicity being significantly associated with JFC. To lower the frequency of JFC among university students, the study emphasizes the urgent need for university-based health promotion and education initiatives.